The Urgency of Developing Instructional Materials for Civic Education Learning in Higher Education - Heny Mulyani; Rahmat; Aim Abdulkarim; Prayoga Bestari; Aura Sabrina Malika (Journal La Edusci, 2026)
Civic Education in higher education is a strategic factor in influencing civic awareness, national commitment, tolerance and character of the students. The actuality of Civic Education is, however, in a way often perceived as a normative and less relevant course because the teaching materials available are not yet rich enough contextually, participatory and connected with the social realities of the students. This paper seeks to explore how important it will be to come up with teaching materials on Civic Education that will be accompanied by the values of religious moderation especially national devotion and tolerance. This research utilized a qualitative research design using case study as its design. Data were gathered via interviews, observation, documentation and field notes and analyzed using the Miles and Huberman model which involves data reduction, displaying data and drawing conclusions. The results indicate that the current Civic Education instructional resources already include the necessary civic issues, including the national identity, democracy, rights and duties of the citizens, the life of a constitutional system, and the multicultural society. Though, these materials remain mostly normative and descriptive, are not adequately tied to learning experiences of students, and have not systematically incorporated values of religious moderation into learning objectives, activities, and assessment. The study concludes that teaching materials in Civic Education should be re-oriented to contextual, participatory and value integrated learning. This kind of development will help reinforce the civic character of students, critical consciousness, devotion to the nation and even tolerance within the multicultural Indonesian society.